Recomposition des territoires en Amazonie brésilienne - Guillaume Leturcq (Confins)
The Brazilian Amazon is a very specific space in relation to the rest of the country. More than a century ago, the Amazon received the impacts of policies and development phases marked subsequently by the rubber cycle, the construction of the TransAmazon Highway, and the implementation of dams and hydropower plants. The analysis of the spacial and scalar impacts of those three fundamental moments in the construction of the modern Amazonian territory is the main objective of this paper. We will use a variety of bibliographic references, historical information combined with fieldwork (including interviews, questionnaires, and both primary and secondary sources) related to the most recent focus of research which has the phase of construction of hydropower plants as main example. Spacial analysis is the basis of the research presented by this paper and its sub-sections follow the main moments of territorial transformations in the Amazon covering a period of about a century.